2016
DOI: 10.4049/jimmunol.1600696
|View full text |Cite
|
Sign up to set email alerts
|

A Novel mTORC1-Dependent, Akt-Independent Pathway Differentiates the Gut Tropism of Regulatory and Conventional CD4 T Cells

Abstract: The vitamin A metabolite all-trans retinoic acid (ATRA) induces a gut-homing phenotype in activated CD4+ conventional T cells (Tconv) by upregulating the integrin α4β7 and the chemokine receptor CCR9. We report that, in contrast to mouse Tconv, only about 50% of regulatory T cells (Treg) upregulate CCR9 when stimulated by physiological levels of ATRA, even though Tconv and Treg express similar levels of the retinoic acid receptor (RAR). The resulting bimodal CCR9 expression is not associated with differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Chen LC et al . [ 110 ] have recently studied CCR9 expression in expanded murine Treg cells showing that only 50% of Treg up-regulate CCR9 when stimulated by atRA. Additionally, they showed that CCR9 and α4β7 do not follow the same signal pathways, whereas the expression of CCR9 is mTORC1-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Chen LC et al . [ 110 ] have recently studied CCR9 expression in expanded murine Treg cells showing that only 50% of Treg up-regulate CCR9 when stimulated by atRA. Additionally, they showed that CCR9 and α4β7 do not follow the same signal pathways, whereas the expression of CCR9 is mTORC1-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…(B) To support the increased need for energy during migration, Treg increase their glycolytic flux. Metabolic shifts in other pathways have not been described for Treg migration (15, 16, 3339). (C) Treg show decreased glycolysis and increased OXPHOS, FAO, FAS and tryptophan metabolism during their phase of suppressive function.…”
Section: Metabolic Pathways Linked To Treg Behavior and Functionmentioning
confidence: 99%
“…Exposure of Treg to the mTOR inhibitor rapamycin suppresses upregulation of both α4β7 and CCR9, suggesting that the mechanism is mTOR-dependent. Strikingly, rapamycin-insensitive companion of mTOR (RICTOR) or (mTORC2)-deficient Treg have unaltered ability to express CCR9, while RAPTOR(mTORC1)-deficient Treg are unable to upregulate CCR9, suggesting the selective participation of mTORC1 in the regulation of Treg motility (39). Loss of phosphatase and tensin homolog (PTEN) also impacts migration by lowering CD62L and CCR7 expression (54).…”
Section: Metabolic Pathways Linked To Treg Behavior and Functionmentioning
confidence: 99%
“…The vitamin A metabolite all-trans retinoic acid (RA) endows guthoming phenotypes in T cells by upregulating the integrin α4β7 and chemokine receptor CCR9. Treatment with rapamycin or RAPTOR deficiency, but not RICTOR deficiency, prevents RA-induced CCR9 expression in Tregs, suggesting that RA promotes gut tropism through mTORC1 [45]. …”
Section: How Is Mtor Activity Regulated In T Cells?mentioning
confidence: 99%